An experimental study on compressive properties of concrete with manufactured sand using different stone powder content. Issue 1 (27th July 2021) - Zheng, Shunyuan; Liang, Junlin; Hu, Yongjun; Wei, Dongyan; Lan, Yifu; Du, Hongliang; Rong, Hongliu
Abstract: Concrete with manufactured sand (MSC) requires adequate compressive properties, which may be caused by stone powder. This present study investigated the effect of different stone powder content (0%, 3%, 5%, 7%, 9% and 11%) on compressive properties of MSC. The properties of fresh MSC were evaluated by three tests, compressive strength, axial compressive strength and elastic modulus. Measure results showed that stone powder as part of fine aggregate replacement improved compressive properties of MSC. The content ranging from 5%–7% increased compressive strength. The content of 11% could greatly improve axial compressive strength. The elastic modulus had a slightly enhancement when the stone powder was within 9%. Predictive models were proposed for the prediction of long-term compressive strength of MSC.